Empire of Serpents (Dragons of Isentol, ,, 2021)
The end draws near. United in their efforts to combat King Torian's evil, Gwen and Conal must now come to terms with the fact that the wicked person responsible for the tyranny and suffering, and the one they seek to destroy, is their uncle. But is being rune-marked with special powers enough to defeat Torian's mages, especially one as powerful as Gimmar the Mage-breaker? When several kingdoms refuse to join their quest, Gwen and Conal find themselves depending on the one race they know they can trust. Dragons. Empire of Serpents is the third book in the series Dragons of Isentol, a tale of dragons, magic, and a growing rebellion against tyranny.

Rune Marked (Dragons of Isentol, ,, 2021)
King Torian's evil is spreading across the realms. Conal and Gwen are hard-pressed to evade Torian's spies and armies while gathering support to combat the evil king's quest for total domination. But they can't do it alone and must seek out the help of dwarves and elves - with unintended consequences. The sudden arrival of dragon-hunters causes some to wonder if the people are filled with madness or if dragons, which were exterminated 150 years ago, might possibly still exist, especially as these fanatics are obsessed with their mission of finding and killing dragons. But why now? What has caused these zealots to abruptly appear, demanding to know where the dragons are? Just when things might be looking up for the rebellion, they discover there are traitors among them. Rune Marked is the second book in the series Dragons of Isentol, a tale of dragons, magic, and a growing rebellion against tyranny.